Increased serum LOXL2 concentration in pelvic inflammatory disease with pelvic adhesion - Chan Xie; Bixin Tang; Kunlun Wu; Qingyi Meng; Fang Wang (BMC, 2022)
Abstract Background Lysyl oxidase-like 2 (LOXL2) belongs to a family of the LOX secretory enzyme, which involves the cross-linkage of extracellular matrix (ECM) proteins. Here, we aimed to analyze the correlation between serum LOXL2 and pelvic adhesion in chronic pelvic inflammatory disease (PID). Methods A total of 143 patients with PID and 130 healthy controls were included in this study. The serum levels of LOXL2 were measured using enzyme-linked immunosorbent assay (ELISA) kits. The patients were divided into non-adhesion group (102 cases) and adhesion group (41 cases). Results It was found that the serum level of LOXL2 expression was elevated in PID patients compared with healthy controls, and was elevated in PID patients with pelvic adhesion compared to patients without adhesion. In all PID patients, serum LOXL2 level was positively correlated with matrix metalloproteinases-9 (MMP-9), transforming growth factor-β (TGF-β1), whole blood viscosity (WBV) at low shear rate (LSR), WBV at high shear rate (HSR), and hematocrit (HcT). Multivariate logistic regression analysis showed that serum LOXL2 level was an independent risk factor for pelvic adhesion in PID patients (OR = 1.058; 95% CI = 1.030-1.086, P < 0.001). Conclusions Serum LOXL2 level not only predicts the presence of PID, but serum LOXL2 concentration is also associated with the presence of pelvic adhesions.